Dosimetric properties of a newly developed thermoluminescent sheet‐type dosimeter for clinical proton beams. Issue 4 (15th March 2021) - Kato, Takahiro; Sagara, Tatsuhiko; Komori, Shinya; Kato, Ryohei; Takeuchi, Akihiko; Narita, Yuki
Abstract: Purpose: This study aimed to evaluate the dosimetric properties of a newly developed thermoluminescent sheet‐type dosimeter (TLD‐sheet) for clinical proton beams. Materials and Methods: The TLD‐sheet is composed mainly of manganese doped lithium triborate, with a physical size and thickness of 150 mm × 150 mm and 0.15 mm respectively. It is flexible and can be cut freely for usage. The TLD‐sheet has an effective atomic number of 7.3 and tissue‐equivalent properties. We tested the reproducibility, fading effect, dose linearity, homogeneity, energy dependence, and water equivalent thickness (WET) of the TLD‐sheet for clinical proton beams. We conducted tests with both unmodulated and modulated proton beams at energies of 150 and 210 MeV. Results: The measurement reproducibility was within 4%, which included the inhomogeneity of the TLD‐sheet. The fading rates were approximately 20% and 30% after 2 and 7 days respectively. The TLD‐sheet showed notable energy dependence in the Bragg peak and distal end of the spread‐out Bragg peak regions. However, the dose–response characteristics of the TLD‐sheet remained linear up to a physical dose of 10 Gy in this study. This linearity was highly superior to those of commonly used radiochromic film. The thin WET of the TLD‐sheet had little effect on the range. Conclusion: Although notable energy dependences were observed in Bragg peak region, the response characteristics examined in this study, such as reproducibility, fading effects, dose linearity, dose homogeneity and WET, showed that the TLD‐sheet can be a useful and effective dosimetry tool. With its flexible and reusable characteristics, it may also be an excellent in vivo skin dosimetry tool for proton therapy.